The Role of Kashiful Qata’s Thoughts and Actions in Resolving the Crises of Fath-Ali Shah Qajar’s Era - Mohammad Mehdi Moradi Khalaj; Mahdi Barzanouni (تاریخ اسلام و ایران, 2024)
Sheikh Ja’far Kashif al-Ghitta (1156-1228 AH), a prominent scholar during the reign of Fath Ali Shah Qajar (1212-1250 AH), significantly impacted the socio-political history of the time. Through his writings and interactions with the Iranian government, he attempted to create a theological framework that combined the authority of the Imam’s representative with the reigning king while actively addressing contemporary crises. His perspectives provide valuable insights into the changes during the early Qajar period.This research utilizes a descriptive-analytical methodology and relies on library sources to analyze Kashif al-Ghitta’s theological thought and political action in response to the social, cultural, and political conditions of his time. It seeks to answer the most important questions: What were the social and political crises of his time? How did he perceive these crises, and what solutions did he propose? Findings indicate that Kashif al-Ghitta was a politically astute jurist who used the principles of Shi'ite ijtihad to bridge ideals and reality. The social and political dynamics of his time motivated his intellectual pursuits. His theoretical and practical approaches not only influenced the changes in his era but also strengthened the Shiite political and theological discourse amidst the challenges of that period.